COVID-19 vaccination in patients with multiple sclerosis: Safety and humoral efficacy of the third booster dose - Dreyer-Alster, Sapir; Menascu, Shay; Mandel, Mathilda; Shirbint, Emanuel; Magalashvili, David; Dolev, Mark; Flechter, Shlomo; Givon, Uri; Guber, Diana; Stern, Yael; Miron, Shmuel; Polliack, Michael; et al. (Journal of the neurological sciences, 2022)
As immunity against SARS-COV-2 wanes following first and second doses of vaccination, a third dose is administered in several countries around the world. Similarly to the first doses, risks related to vaccination and humoral immune response in patients with multiple sclerosis (MS) need to be assessed. Characterize safety and humoral immune response following the third dose of COVID-19 vaccination in a large cohort of MS patients. We assessed the safety of the third dose of the BNT162b2-COVID-19 mRNA vaccination in adult MS patients and evaluated SARS-CoV-2 IgG response. Two hundred and eleven adult MS patients received a third dose of BNT162b2 COVID-19 vaccination. Median follow up time was 66 days from vaccine administration (IQR 54–84). The frequency of any adverse event was 54.5%, with the most common reported adverse events being fatigue, local pain at the injection site, fever and muscle or joint pain. Transient increase in MS symptoms was reported in 3.8% of patients, none of them requiring treatment. The rate of acute relapses treated with IV steroids was 3.3%. In a sub-group of 55 patients, 20 untreated and 35 treated with vaccination-safe disease-modifying treatments, SARS-CoV-2 IgG levels increased 21-fold (median ± SD 21.6 ± 53.05). The third dose of COVID-19-BNT162b2 vaccine proved safe for MS patients, with no increased risk of relapse activity. Untreated patients and patients treated with vaccination-safe disease-modifying treatments show significant increase in SARS-CoV-2 IgG levels following the third dose of vaccination. •The third dose resulted in adverse events profile similar to that following the first and second doses.•No increased risk for relapse activity following the third vaccine dose was observed within a follow-up of 2 months.•Paired kinetics of anti-spike IgG titers revealed a 21-fold increase in up to 3 months following the third dose.•This finding held true both in untreated and in vaccination–safe DMTs treated MS patients.